Towards an understanding of the geographical background of plants invasion as a natural hazard: a case study in Hungary - Dr. Szilassi, Péter; Visztra, Georgina Veronika; Soóky, Anna; Bátori, Zoltán; Hábenczyus, Alida Anna; Frei, Kata; Tölgyesi, Csaba; Balogh, Márton Bence (Geographica Pannonica, 2022)
Biological invasion is a worldwide phenomenon that can be considered a natural hazard. Protection against invasive plant species can only be successful if we know the anthropogenic factors that influence their occurrence, such as changes in land cover. In our study, we investigated the LUCAS based spatial distribution of five common invasive plant species (2015) and its connections with the recent (2012-2018) land CORINE based cover changes. The LUCAS points infected with this species are much closer to the CORINE land cover change polygons than the non-infected points. Our results suggest that the occurrence of Asclepias syriaca, Solidago spp, Ailanthus altissima and Robinia pseudoacacia is significantly dependent on whether land use has changed in the vicinity of LUCAS points infected with these species. Only the occurrence of Elaeagnus angustifolia does not show any correlation with changes in land cover.